Power and energy [1999 technology analysis and forecast]. - Sweet, W. (IEEE spectrum)
This article presents a power and energy technology analysis and forecast for 1999. The subjects covered include photovoltaics, PV power systems, solar arrays, nuclear power and free market spot electricity pricing